Species Diversity of Epiphyte Fern Plants in Curug Lawe Waterfall Region, Semarang District - Rizky Wahyu Saputro; Sri Utami; Lilih Khotimperwati (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
Epiphyte fern plants are fern plants that grow attached to the phorophyte tree. Existence of fern plants are effected by tree bark and environmental condition in which they grow. This research aimed to study the species composition, important value index, diversity index, evenness index, and similarity index of epiphyte fern plants in the Curug Lawe Waterfall Region Semarang District. This research was conducted on 5 research stations i.e. clove plantations area (CPA), irrigation canal (IC), mixed forest (MF), river flow (RF), and waterfall area (WA). The research used plot technique with plot size 10 m x 10 m. The results showed 11 species of epiphyte fern from 8 families were found. The highest important value index is obtained by Goniophlebium serratifolium. The diversity index of epiphyte fern plants are categorized as low and moderate. The evenness index of epiphyte fern plants are categorized as not evenly distributed, quite evenly distributed, and almost evenly distributed. The highest similarity index is in irrigation canal (IC) and river flow (RF). Environmental conditions in Curug Lawe Waterfall Region are suitable for epiphyte fern plants habitat. This research is novel as it provides some information about the community structure of epiphyte ferns in Curug Lawe Waterfall Region and to engage all peoples to maintain our biodiversity keep sustainable.